Defect characteristic of oxygen-deficient Ge-doped preform using photoluminescence spectroscopy - Siti Shafiqah, A.S.; Sani, S.F. A.; Tamchek, N.; Almugren, K.S.; Alkallas, F.H.; Bradley, D.A. * (Elsevier, 2023)
Study has been made of the Photoluminescence properties of Ge-doped silica preforms fabricated using the MCVD process and subsequently subjected to γ-ray irradiation. The photoluminescence emissions pointed to the presence of defects related to oxygen vacancies. Two types of preform were fabricated, obtained using a different flow rate and deposition temperature for each case. Results from the absorption spectra of the samples named as P1 and P2, show a signature absorption peak at 5.1 eV and 6.8 eV, indicative of oxygen-deficient and oxygen-rich defects respectively. Photoluminescence investigation have been carried out before and after the irradiation process with both samples reveal two main peaks at 1.5 eV. The highest intensity at 1.5 eV is known as an interaction between the Non- Bridging Oxygen Hole Centre (NBHOC) with the presence of impurity in the glass matrix. Upon irradiation, weak peak can be observed at 1.8 eV, sample P1 and P2, the PL intensity increases by a factor of 20 × and 50 × , respectively. This peak is associated with the oxygen deficient state in the sample. The peak referring to defect known as Germanium Lone Pair Centre (GLPC) are observed in both samples, peak shown at 3.1 eV, regardless of the Germanium Oxygen Deficient Centre (GODC) content. In regard to this, it can be concluded that this defect is generated independently in all germanium samples and are not correlated with the GODC band observed in the absorption band.